2010
DOI: 10.1073/pnas.0912675107
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of IL-17A abrogates progression of spontaneous intestinal tumorigenesis

Abstract: The intrinsic role of endogenous IL-17A in spontaneous intestinal tumorigenesis has not been addressed previously to our knowledge. Ablation of IL-17A significantly reduced tumor development in mice bearing a heterozygote mutation in the adenomatous polyposis coli (APC) gene (Apc Min/+ mice). There was also a decrease in inflammatory cytokines and proinflammatory mediators, reduced infiltration of lymphocytes including T cells, and preservation of intestinal architecture and the presence of APC protein in inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
164
4
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(188 citation statements)
references
References 24 publications
14
164
4
1
Order By: Relevance
“…Il17a deficiency reduces intestinal tumorigenesis in both colitis-associated and spontaneous intestinal cancer mouse models. 127,128 The loss of IL-23 signaling, which is critical for the generation of pathogenic Th17 responses, inhibits tumor growth in a spontaneous colon cancer mouse model; this finding is in agreement with the phenotype of Il17a-deficient mice. 129 As a consequence of the genetic lesions of colorectal cancer, either the early or late stage of colorectal tumors exhibit defects in their epithelial barrier integrity.…”
Section: Il-17dsupporting
confidence: 72%
“…Il17a deficiency reduces intestinal tumorigenesis in both colitis-associated and spontaneous intestinal cancer mouse models. 127,128 The loss of IL-23 signaling, which is critical for the generation of pathogenic Th17 responses, inhibits tumor growth in a spontaneous colon cancer mouse model; this finding is in agreement with the phenotype of Il17a-deficient mice. 129 As a consequence of the genetic lesions of colorectal cancer, either the early or late stage of colorectal tumors exhibit defects in their epithelial barrier integrity.…”
Section: Il-17dsupporting
confidence: 72%
“…For example, the adoptive transfer of IL-17-producing CD4 (+) (Th17) cells has been shown to promote either tumor development or tumor regression (58)(59)(60). And IL-17(R) deficiency/blockade was associated with both enhanced (61) and reduced (23,(62)(63)(64) tumor load. The reasons for the highly variable anti-versus protumor activities of IL-17 and IL-17-producing T cells in distinct tumor models remain unclear and deserve further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Although Th17 cells have been shown to promote cytotoxic T cell responses in a model of melanoma metastasis 24 , IL-17A has been found to favour tumour development in other models [25][26][27] . In fact, it has been previously reported that IL-17A boosts tumour development by inducing a tumour-promoting microenvironment 25 and that targeted deletion of IL-17A suppresses intestinal tumourigenesis 26 .…”
Section: Ifn-g Production In Lung Cd8mentioning
confidence: 99%
“…In fact, it has been previously reported that IL-17A boosts tumour development by inducing a tumour-promoting microenvironment 25 and that targeted deletion of IL-17A suppresses intestinal tumourigenesis 26 . Consistent with a pro-tumour function of IL-17A, it has also been reported that IL-17A expression is regulated by STAT3, a protooncogene activated by IL-6 in tumour and tumour stromal cells, promoting tumour cell survival, proliferation and angiogenesis 28,29 .…”
Section: Ifn-g Production In Lung Cd8mentioning
confidence: 99%